امام عبدالوہاب شعرانی: تصانیف اور نمایاں افکار کا تعارف: Abdul Wahāb Shaʻrānī: An Introduction to Writings and Important thoughts - Dr. Saeed Ahmed Saeedi; Dr. Aijaz Ali Khoso (Al-Qamar, 2020)
This article presents a review of Abdul Wahāb Shaʻrānī’s spiritual, intellectual and innovative achievements along with a brief introduction of his potentials. It finds that Shaʻrānī was one of the versatile personalities of Islamic history. He was Imām of Sharīʻah as well as Tarīqah; he removed the contradictions between Sharīʻah and Tarīqah. To him the real Sufism was to protect the body from the lusts, to purify the heart, to worship Allah Almighty with sincerity and to follow the path of the Prophet (ﷺ). He for the first time presented the theory of Mīzān for the unity of Muslim Ummah. He declared the differences between the Imāms of the different schools of jurisprudence as mercy. Shaʻrānī didn’t get lost in the colorfulness and charm of life, but make sincerity and divinity, constant struggle and trust in Allah as his motto. The sole purpose of his life was to gain the pleasure of God and the reformation and guidance of God’s creatures. He clarified that all Islamic sciences were the means to reach God, not the goal itself. Therefore, one should always keep in mind the attainment of the purpose of "Reaching Allah Almighty" through these sciences.